2002
DOI: 10.1111/1475-6811.00009
|View full text |Cite
|
Sign up to set email alerts
|

Emphatic inaccuracy in husband to wife aggression: The overattribution bias

Abstract: Is husbands' wife-directed aggression related to unusual accuracy (hypersensitivity) or to bias (being likely to inappropriately infer criticism or rejection) when they infer women's critical/rejecting thoughts and feelings? Results of a study using the empathic accuracy paradigm and signal detection analyses revealed that the greater the husbands' bias to overattribute criticism and rejection to the thoughts and feelings of women they had never met, the more the husbands reported behaving in a verbally aggres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 48 publications
6
42
2
1
Order By: Relevance
“…For instance, maritally abusive men score lower on empathic accuracy than non-abusive men [153]. This suggests that enhancing empathic accuracy can potentially reduce marital abuse.…”
Section: Cognitive Empathymentioning
confidence: 99%
“…For instance, maritally abusive men score lower on empathic accuracy than non-abusive men [153]. This suggests that enhancing empathic accuracy can potentially reduce marital abuse.…”
Section: Cognitive Empathymentioning
confidence: 99%
“…On the other hand, some research has shown that high levels of victim-blaming are associated with increased intimate partner abuse [42]. Studies on attributions in relationships show that men who have been violent in their relationships tend to view their partners as critical, rejecting, and intentionally malicious, and tend to blame their partners for difficulties [43][44][45]. Finally, with regard to minimization, as Scott and Straus [18] point out, individuals with prior experience of intimate partner violence are more likely to minimize the extent and impact of low-level abusive behaviors [46] and to be accepting aggression in relationships [47][48].…”
Section: Batterer Programs and Assumption Of Responsibilitymentioning
confidence: 99%
“…There is a precedent in the research literature for the procedures we have used. A similar signal detection approach to analyze data generated within an empathic accuracy paradigm has previously been reported by Schweinle, Ickes, and Bernstein (2002).…”
Section: Signal Detection Analysismentioning
confidence: 99%